Commercialization of products with territorial identity in the Cristobal Colon Agricultural and Livestock Association (Revista Científica Interdisciplinaria Investigación y Saberes, 2022)
The objective of the research is to identify factors related to the commercialization of the production of different products sold by the Asociación Agropecuaria Cristóbal Colón. Small farmers and ranchers enter different programs offered by MAGAP in the Province of Santo Domingo de los Tsáchilas, including the Parish of Valle Hermoso, in order to get help and advice for their businesses, while most have problems when determining the costs of their products, because there is no business model within the national market, including the planning and evaluation of products to perform accounting processes with more continuity, how to know what are their investment costs, expenses and what is the profit that each business has. Through this study of the cost of production it is possible to identify that the different merchants should have an adequate model on how to carry out an accounting and taxation process more frequently.  A survey was applied to 23 members of the "Cristobal Colon" Association of the Parish of Valle Hermoso, obtaining as a result that milk occupies the first place as a product with territorial identity, followed by cocoa, palm heart and coffee, which are relevant for the economy of the Parish of Valle Hermoso.